2018
DOI: 10.1007/s11136-018-2039-5
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and service satisfaction in outpatients with severe or non-severe mental illness diagnoses

Abstract: Purpose Our study investigated quality of life (QoL) in patients with severe or non-severe mental illness diagnoses (SMI and non-SMI) and the association between QoL and service satisfaction measured as patients’ perception of continuity of care (CoC), therapeutic relationship, and unmet service needs. Methods We conducted a national cross-sectional survey among 3836 mental health outpatients, of whom 1327 (34.6%) responded. We assessed QoL with the Manchester Short Ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 43 publications
1
12
0
3
Order By: Relevance
“…This study adds to this known literature by exploring more clinical and service characteristics as opposed to individual factors. However, from the available clinical and demographic variables findings were in line with previous research, for example, we found higher satisfaction with life aspects in patients with psychotic disorders compared to mood or neurotic diagnoses [ 25 28 ]. Results from experimental studies have suggested that this is because affective states inform and direct judgements on satisfaction [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…This study adds to this known literature by exploring more clinical and service characteristics as opposed to individual factors. However, from the available clinical and demographic variables findings were in line with previous research, for example, we found higher satisfaction with life aspects in patients with psychotic disorders compared to mood or neurotic diagnoses [ 25 28 ]. Results from experimental studies have suggested that this is because affective states inform and direct judgements on satisfaction [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Ådnanes et al. (2019) conducted a study that investigated satisfaction with the health services among people with a mental disorder, whether severe or non‐severe, among other aspects. The authors concluded that PLSMI had a worse connection with health services and that, to address this problem, these services needed to enhance the involvement of these people and their perspectives in the treatment process, since this increases not only their satisfaction, but also their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review that evaluated self-management approaches in persons with a SMI included the evaluation of educational efforts in improving Quality of Life and Symptomatic outcomes and reported only a small effect of educational efforts on the perceived outcomes [ 64 ]. Additionally, several studies emphasize the importance of social contacts in continuity of care, and contacts with peer coaches provides a solid base for trustworthiness and commitment in people with a SMI [ 65 , 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%